Adsorbent from coffee grounds to reduce cadmium concentration in leachate water - Syamsuddin Suaebu; Ashari Rasjid; Iwan Suryadi (International Journal of Advances in Applied Sciences, 2024)
Wastewater contains a variety of heavy metals, one of which is cadmium (Cd) which causes adverse effects on both the environment and health. Coffee grounds can be used to reduce Cd in wastewater so this study aims to determine the reduction of Cd levels using coffee grounds. The type of research used is an experiment to see the decrease in Cd levels using carbonized and non-carbonized coffee grounds. The samples used were taken from the leachate water source at one of the landfills in Makassar City. Sampling was done using the grab sampling technique. The results showed that the use of uncarbonized and carbonized coffee grounds was effective in reducing Cd levels in Makassar City Tamangapa Landfill leachate water with an average decrease of 0.048 and 0.023 µg/L. Uncarbonized coffee grounds have a higher ability to reduce Cd in leachate so that it can be used as an alternative in the wastewater treatment process.